Perceived organisational support and employees' performance: the mediating role of affective commitment. (17th July 2020) - Yücel, İlhami; Ribeiro, Neuza; Gomes, Daniel Roque
This paper aims to understand if workers' affective commitment (AC) mediates the relationship between perceived organisational support (POS) and individual performance (IP). Using a sample of 476 professionals of a Turkish hospital, structural equation modelling was used to test for the model of analysis. Results revealed that: 1) POS is positively related with employees' AC; 2) POS is positively related with IP; 3) AC is positively related with IP; 4) AC fully mediates the relationship between POS and IP. This study suggests that supporting employees is a valid path for the development of an affective bond with the organisation, which in turn fosters employees' effectiveness.